Antibacterial efficacy of Streptomyces maritimus SACC-E6 against carbapenem-resistant Klebsiella pneumoniae ATCC BAA-1705 - Radhakrishnan Manikkam, Vijayalakshmi Ganesan, Manigundan Kaari, Gopikrishnan Venugopal, Suresh Arumugam, Jerrine Joseph (Journal of Applied Pharmaceutical Science, 2021)
Klebsiella pneumoniae that is resistant to carbapenem antibiotic has emerged as the fourth common cause of pneumonia in intensive care units. There is a dire need for unique antibiotics since the treatment options for Carbapenem resistant - Klebsiella pneumoniae (CR-KP) are very limited. Ninety eight marine actinobacterial strains were screened for antibacterial efficacy against carbapenem-resistant K. pneumoniae ATCC BAA-1705, in which strain SACC-E6 showed a maximum of 20 mm zone of inhibition. Active molecules from strain SACC E6 was extracted with organic solvents, such as methanol, chloroform, ethyl acetate, and n-hexane, by solid liquid extraction method. Antibacterial activity of all the extracts was tested by the paper disk diffusion method at a concentration of 100 μg/disk. Methanolic extract of the strain SACC-E6 showed a maximum of 24 mm inhibition. Two active molecules from the methanol extract of strain SACC-E6 were detected by thin layer chromatography-based bioautogram. The taxonomical investigation revealed that strain SACC E6 was Streptomyces maritimus. According to the literature, only 1.5% of actinobacteria from any ecosystem was found be active against Gram-negative bacterial pathogens. Interestingly, around 31.63% of marine actinobacterial strains showed activity against CR-KP. Also, the results showed that marine S. maritimus SACC-E6 is a reliable resource for the anti-infective molecules effective against K. pneumoniae that is resistant to carbapenem antibiotic.
Keywords: Carbapenem-resistant, Klebsiella pneumoniae, Streptomyces maritimus, anti-bacterial, bioautogram.